Ionic liquid—a future solvent for the enhanced uses of wood biomass - Man, Zakaria (Springer-Verlag 2011, 2012)
Biomass refers to biological materials that can be used as fuel or for the production of chemicals. Globally, ever growing demand of energy and concerns for the environment have prompted researchers to develop convenient and efficient ways for converting wood biomass into valuable chemicals, bio-fuels and useful biomaterials. In this context, ionic liquid has the potential to play a major role. Ionic liquids, considered as green solvents, have been found capable of dissolving wood biomass, and the dissolution process can be enhanced in a number of ways, like heating, microwave treatment, addition of acids etc. The anionic part of ionic liquid plays an important role in this process coupled with hydrogen bond basicity (β) property of ionic liquid, which has a significant effect on wood biomass dissolution. This paper reviews the applications of ionic liquids for the dissolution, fractionation and regeneration of wood biomass. It is also related to the processing of cellulose and wood biomass, preparation of cellulose and wood biomass derivatives and composites Nawshad Muhammad · Zakaria Man · Mohamad Azmi Bustam Khalil